The Feasibility of using Internet of Things in Higher Education Institutions - F. Jarallah , Luma; A. Alyouzbaky , Bassam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The Internet of Things (IoT) is a modern phenomenon that is used in a variety of industries, including intelligent transportation, smart cities, healthcare, games, and education. The use of IoT applications to enhance the quality of higher education has become a crucial subject in the discipline of teaching research. The objective of this research is to find out whether educational institutions could incorporate higher education and the Internet of Things by utilizing the technological acceptance model. For the purpose of achieving this, the University of Mosul was chosen to identify the position of faculty members in this field. The study proposes a model consisting of factors adopted from the TAM Theories. A quantitative approach has been used in this study; the questionnaire has collected data from the research sample, and a random sample of 99 participants was selected. Data analysis was carried out using SPSS 26 and Smart Partial Least Squares (SmartPLS4) packages. According to the findings of this research, the perception of benefit is influenced by ease of use. In contrast, self-efficacy and facilitation conditions are unchanged and do not affect behavioral intention to adopt the Internet of Things. The study suggested the need to hold workshops and training courses for academic staff in the field of Internet of Things applications.